Belgian Royal Couple visit IITA-DRC - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Catch up with highlights of the visit of the Belgian Royal Couple, King Philippe and Queen Mathilde, to IITA President Olusegun Obasanjo Station, Kalambo, Democratic Republic of Congo:- Le Roi et la Reine